Determinan niat pengusaha untuk menggunakan pembiayaan bagi hasil - Cahya Buditama (Proceeding of National Conference on Accounting & Finance, 2020)
This study contributes to the general understanding of the intention of entrepreneurs to use the services of banks / Islamic financial institutions especially on profit-sharing products. Although financing at Islamic banks is currently developing quite significantly, the financing is more dominated by financing with sale, lease and other contracts. Whereas the contract for the results showed very little development. This is inseparable from the small number of products that are determined to be successful and the difficulty of intensive management and the role of trust of each party is very small. Whereas with the agreement of the results, it actually shows more the concept of applying the principles of sharia which is more just and of course in the real private sector it will be very good to develop potential / income in several other sectors. Research has contributed to the expansion of the Theory of Reasoned Action (TRA) model, namely Theory of Planned Behavior (TPB) and the additional variable factors directly affect the intention of entrepreneurs to buy profit-sharing financing schemes namely Social Cognitive Theory (SCT). From the synthesis of theoretical models and based on previous studies, this study has proposed a research model for individual variables. Once again, based on the results of the data analysis process, this research has identified attitudes, perceived behavioral control, subjective norms affecting intention. In conclusion, although this research is still limited, the results will contribute to providing a basis for decision making for banks regarding profit-sharing financing products that are still very limited in their products, while it is useful for marketers to be able to find solutions for marketing impact and promote the seller's intention to use financing profit sharing. Suggestions for future researchers, can conduct similar research by developing in a wider lang location, so as to be able to give a practical picture in different locations so that it can add to existing toritis references.